PRODUCTION RESPONSE TO PRICES IN THE COCONUT INDUSTRY OF PAPUA NEW GUINEA: A COMMENT ON THE METHODOLOGY AND A RE ESTIMATION - Premasiri J. Gunawardana (International Coconut Community Journal, 1988)
Analytical studies on the supply response of growers in the major crop sectors in Papua New Guinea (PNG) are scarce. For this reason, De Silva, Kiele and Lagap (DKL, 1987) must be congratulated for their pioneering attempt at analysing the production response to changes in prices in the coconut sector of the country. However, in their analysis there are several short‑comings of a methodological and empirical nature. The purpose of this note is to highlight these shortcomings and offer altemative estimations and interpretations about the nature of production response to price changes in the coconut sector.